2016
DOI: 10.4103/1008-682x.165948
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities between extremely severe oligozoospermia and cryptozoospermia in intracytoplasmic sperm injection

Abstract: Patients with extremely severe oligozoospermia (ESO) and cryptozoospermia (CO) are suitable using intracytoplasmic sperm injection (ICSI) as an infertility treatment. However, some andrologists are confused to distinguish ESO and CO in clinic diagnose. This study was designed for the first time to evaluate and compare patients with ESO and CO to determine whether these are useful clinical distinctions. A total of 270 infertile men in our center were classified into four groups as Group nonobstruction azoosperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…FSH has considerable biological role in testicular function. Lacking of FSH would shorten testis size, sperm concentration and sperm motility, so FSH plays a important role in boosting cells proliferation and is desired for normal sperm production [ 12 ]. FSH induces the Sertoli cells to secrete inhibin and androgen-binding protein and plays a major role in initiation and progression of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FSH has considerable biological role in testicular function. Lacking of FSH would shorten testis size, sperm concentration and sperm motility, so FSH plays a important role in boosting cells proliferation and is desired for normal sperm production [ 12 ]. FSH induces the Sertoli cells to secrete inhibin and androgen-binding protein and plays a major role in initiation and progression of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for the drug group were: (1) had ejaculation by masturbation successfully more than twice, (2) were not able to ejaculation on the day of oocyte retrieval, (3) sperm were identified on semen analyses. Inclusion criteria for the control group were: (1) previously identified azoospermia, which contained obstruction azoospermia and non- obstruction azoospermia, or cryptozoospermia [ 2 ], (2) testis volumes were more than 8 mL. Patients in the drug group were all sperm retrieval performed by TESA successfully.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the prostate gland and dorsal prostatic secretions, which are required for sperm motility, had morphological prostate alterations and secretion modification at aging rats Also, the study results showed a link between sperm immobility and motility and a failure in the prostatic function in old male rats, when sperm motility was decreased at both 12 months, 24 months of age (Lucio., et al 2013) (Figure 2). Moreover, any medicine, tumour, illness, or disorder that influences the pituitary gland or hypothalamus could be a potential cause of male infertility through modifying gonadotropic releasing hormone or producing gonadotropin as idiopathic hypogonadotropic hypogonadism (IHH), Kallmann syndrome (IHH with anosmia), and mixed pituitary hormone deficiency (Leslie SW., et al [3]. In addition, pituitary tumours like sellar tumours, macroadenomas, and prolactinomas can also rise in male infertility due to changes in gonadotropin hormone production and Besides, sev-eral genetic causes Prader-Willi, Young, and Laurence-Moon-Biedl syndromes, can lead to male infertility.…”
Section: Male Infertilitymentioning
confidence: 99%
“…centration; this condition is diagnosed as a severe oligozoospermia (ESO)(Deng., et al 2015) [5]. ESO that has not been described by the World Health Organization is explicitly a state that spermatozoa concentration is <1 × 106 ml−1, based on the definition of severe oligoasthenoteratozoospermia by various studies.…”
mentioning
confidence: 99%